Screeining of fibrinolytic protease from south indian isolates of ganoderma lucidum - S. KUMARAN; P. PALANI; C. CHELLARAM; T. PREM ANAND; V. KAVIYARASAN (International Journal of Pharma and Bio Sciences, 2011)
Intravascular thrombosis due to fibrin aggregation in arteries is one of the main causes of cardiovascular disease in humans. Thrombolytic agents such as heparin and Streptokinase have been extensively used in the therapeutic treatment of thrombosis. Search for potent and effective thrombolytic agents from various sources such as bacteria and fungi continue around the world. In the present study, Ganoderma lucidum a higher fungus has been studied for the optimal production of fibrinolytic protease. The physical parameter been identified and standardized for optimal production of biomass and intracellular fibrinolytic protease. The medium composition and design of fermentation condition play vital role in enhancing the efficiency of biomass and by-product production. Out of eight media tested the maximum mycelial biomass of 15 g/L was obtained on day 21 of incubation when the test fungus G. lucidum was grown on fibrin amended potato dextrose broth. Of all the 24 isolates grown on fibrin amended PDA, it was found that the strain VK 12 isolated from Tamarindus indica showed faster growth rate and maximum protease production.